Supply Chain Management of Coats Bangladesh Ltd. - Jameo, Sk Abdullah Al (BRAC University, 2016)
This thesis is restricted.This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.